LEGAL LIABILITY OF THE SCHOOL OPERATIONAL ASSISTANCE TEAM IN GOODS AND SERVICES PROCUREMENT THROUGH SIPLAH: DEFAULT AND DISPUTE RESOLUTION PERSPECTIVE - Wan Iswandi; Nurjannah Septyanun; Yulias Erwin (Jurnal Ilmiah Advokasi, 2026)
This research analyses the legal implications for SOA  (School Operational Assistance) Teams and goods/service providers via SIPLAH (Sistem Informasi Pengadaan di Sekolah - School Procurement Information System) in cases of default, and examines the available dispute resolution mechanisms. The background to this issue is the high potential for disputes arising in educational goods and services procurement transactions facilitated by the SIPLAH system, given the complexity of the parties involved and the substance of the contracts. This study employs a juridical-normative approach by reviewing relevant laws and regulations, including those concerning School Operational Assistance (SOA) Funds and government goods and services procurement, as well as civil law principles, particularly regarding contracts and default. Data was obtained through a literature study and legal document analysis. The research findings indicate that default by either the SOA  Team or a SIPLAH provider can lead to various legal consequences, ranging from compensation obligations and contract cancellation to administrative and criminal sanctions, depending on the nature and impact of the default. The dispute resolution mechanisms that can be pursued include amicable settlement (musyawarah mufakat), mediation, arbitration, or litigation through the district court. A deep understanding of the rights and obligations of the parties, as well as dispute resolution procedures, is expected to minimise the risk of default and ensure the effectiveness and accountability of SOA  Fund utilisation. This study contributes to the development of legal doctrine regarding the legal responsibilities of School Operational Assistance Teams in electronic procurement through SIPLAH by clarifying the legal consequences of default and proposing a more effective dispute resolution framework.Keywords: Default, SOA  Team, SIPLAH, Dispute Resolution, SOA  Fund.